Stereospecific lactylation in bacteriology: L/D-lactate partitioning shapes host metabolic-disease axis - Wang, Sirui; Zhang, Leiliang (Frontiers in Microbiology, 2025)
Two stereoisomers of lactate, L- and D-lactate, serve as critical conduits for bidirectional communication in host-bacteria interactions and the development of diseases. Lactylation, a novel post-translational modification (PTM), has been linked to the regulation of gene expression, immune responses, and pathogen virulence. This review examines the metabolic pathways of L- and D-lactate, their associated lactylation modifications (KL-la, KD-la, and Kce), and the regulatory mechanisms underlying these processes. We highlight the distinct roles of L- and D-lactate in bacterial metabolism and the implications of lactylation in bacterial infections, exploring their multifaceted impacts on diseases such as infections, metabolic disorders, and neurodegenerative conditions. This review presents novel strategies for targeting stereospecific lactate metabolism and lactylation, and it summarizes key methods for detecting both lactate isomers. Additionally, it provides insights into their clinical applications and outlines future research directions within the context of bacterial-related diseases.